Combined Analysis of Serum Alpha-Fetoprotein and MAGE-A3-Specific Cytotoxic T Lymphocytes in Peripheral Blood for Diagnosis of Hepatocellular Carcinoma. Issue 6 (22nd December 2013) - Cui, Zhuqingqing; Yu, Xin; Guo, Limin; Wei, Yuhua; Zheng, Shengmin; Li, Wenxia; Chen, Pengcheng; Zhu, Jiye; Peng, Jirun
Abstract : We investigated the feasibility of the combined detection of HLA-A2/MAGE-A3 epitope-specific cytotoxic T lymphocytes (CTLs) and serum alpha-fetoprotein (AFP) for specific diagnosis of hepatocellular carcinoma (HCC). We detected the frequency of MAGE-A3 epitopes (p112–120, KVAELVHFL) in spontaneous CTLs in the peripheral blood of HCC patients, liver cirrhosis patients, and healthy subjects with HLA-A2/polypeptide complex (pentamer) detection technology. Eighty-five HCC cases, 38 liver cirrhosis cases, and 50 healthy cases who were HLA-A2-positive were selected from 175 HCC patients, 80 patients with liver cirrhosis, and 105 healthy volunteers, respectively. The frequency of HLA-A2-specific MAGE-A3 + CTLs in the HCC group was significantly higher than that in the other groups. Combined detection of MAGE-A3 + CTL frequency and serum AFP value had a higher specificity than either of the two indicators alone. The pentamer technique is helpful in distinguishing benign lesions and malignant lesions in the liver. Combined with serum AFP, it can improve the diagnosis performance for HCC, especially for AFP-negative cancer.